Materials Science and Technology 2012
DOI: 10.1002/9783527603978.mst0430
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ADMET Polycondensation Chemistry

Abstract: The sections in this article are Introduction Functionalized Polyethylenes Linear Ethylene/Vinyl Ether Copolymers Linear Ethylene/Acrylic Acid Copolymers Phosphonic Acid‐Functionalized Polyethylenes Functional Polymers and Materials via ADMET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…56 Additionally, Altintas et al reported a polymer folded by two different orthogonal hydrogen bonding dimers. Combining SCNP synthesis techniques with advanced polymer syntheses that control monomer sequence or functional group placement such as work by Perrier, 12 Lutz, 14 and Whittaker, 73 or well-defined step-growth chemistry such as ADMET, 13 provides possibilities that could take the current state of the art one step closer to the structural precision found in natural folded macromolecules. 63 Outlook Surveying the literature it becomes clear that SCNP synthesis using a singular covalent chemistry as an intra-chain crosslink, and even the use of dynamic covalent chemistry or various supramolecular interactions is a well developed, proven technique.…”
Section: Multiple Intra-chain Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Additionally, Altintas et al reported a polymer folded by two different orthogonal hydrogen bonding dimers. Combining SCNP synthesis techniques with advanced polymer syntheses that control monomer sequence or functional group placement such as work by Perrier, 12 Lutz, 14 and Whittaker, 73 or well-defined step-growth chemistry such as ADMET, 13 provides possibilities that could take the current state of the art one step closer to the structural precision found in natural folded macromolecules. 63 Outlook Surveying the literature it becomes clear that SCNP synthesis using a singular covalent chemistry as an intra-chain crosslink, and even the use of dynamic covalent chemistry or various supramolecular interactions is a well developed, proven technique.…”
Section: Multiple Intra-chain Interactionsmentioning
confidence: 99%
“…Recent advances in contemporary controlled polymerization chemistry allow the synthesis of multiblock polymers with narrow molecular weight distributions 12 or materials with controlled monomer sequences 13,14 by step-growth and chain-growth methods. Tertiary structure is permitted by a pristine primary structure, a quality that is currently inaccessible in synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Acyclic diene metathesis (ADMET) polymerization has been a promising method for synthesis of high molecular weight poly­(2,5-dialkyl­phenylene-1,4-vinylene)­s (PPVs), PFVs, and poly­( N -alkyl­carbazole-2,7-vinylene)­s. This is because the approach affords defect (impurities such as halogen sulfur, etc., and/or regio-/stereoirregularity, cross-linking, etc.) free, stereoregular ( all - trans ) materials which are difficult from those by adopting the conventional condensation (dehalogenation–condensation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…These precise polyethylenes are synthesized via acyclic diene metathesis (ADMET) polymerization, a technique that provides remarkable control over polymer microstructure but remains challenging to scale up to industrially relevant levels of production. To capitalize on the attractive properties discovered in ADMET polymers, more scalable synthetic routes are desired.…”
mentioning
confidence: 99%